Dedicated software to harmonize the follow-up of oncological patients - Mathias Illy; Axel Bartoli; Julien Mancini; Florence Duffaud; Vincent Vidal; Farouk Tradi (Research in Diagnostic and Interventional Imaging)
Objective: To test and evaluate a sofware dedicated to the follow-up of oncological CT scans for potential use in the Radiology department. Materials and methods: In this retrospective study, 37 oncological patients with baseline and follow-up CT scans were reinterpreted using a dedicated software. Baseline CT scans were chosen from the imaging reports available in our PACS (picture archiving and communicatin systems). Follow-up interpretations were independently assessed with the software. We evaluated the target lesion sums and the tumor response based on RECIST 1.1 (Response Evaluation Criteria in Solid Tumors). Results: There was no significant difference in the target lesion sums and the tumor response assessments between the PACS data and the imaging software. There was no over or underestimation of the disease with the software. There was a sigificant deviation (progression versus stability) in three cases. For two patients, this difference was related to the evaluation of the response of non-target lesions. The difference in the third patient was due to comparison with a previous CT scan than to the baseline exam. There was a miscalculation in 13 % of the reports and in 28 % of the cases the examination was compared to the previous CT scan. Finally, the tumor response was not detailed in 43 % of the follow-up reports. Conclusion: The use of dedicated oncology monitoring software could help in reducing intepretation time and in limiting human errors.